2018
DOI: 10.1007/s41542-018-0011-y
|View full text |Cite
|
Sign up to set email alerts
|

Applying the Precaution Adoption Process Model to the Acceptance of Mine Safety and Health Technologies

Abstract: Mineworkers are continually introduced to protective technologies on the job. Yet, their perceptions toward the technologies are often not addressed until they are actively trying to use them, which may halt safe technology adoption and associated work practices. This study explored management and worker perspectives toward three technologies to forecast adoption and behavioral intention on the job. Interviews and focus groups were conducted with 21 mineworkers and 19 mine managers to determine the adoption pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This phenomenon can also be explained in this way: the perception of risk magnitude is not only determined by its impact; it is also influenced by a firm’s ability to treat the different risks that arise. In addition, the ability of enterprises to deal with risks is also at the core of enterprise trust, which is also an important reason behind the observed cognitive differences between the managers and miners, as they have different initial levels of trust in their respective enterprises [ 19 ]. This result reminds enterprises to pay attention to improving their image of in the minds of miners.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon can also be explained in this way: the perception of risk magnitude is not only determined by its impact; it is also influenced by a firm’s ability to treat the different risks that arise. In addition, the ability of enterprises to deal with risks is also at the core of enterprise trust, which is also an important reason behind the observed cognitive differences between the managers and miners, as they have different initial levels of trust in their respective enterprises [ 19 ]. This result reminds enterprises to pay attention to improving their image of in the minds of miners.…”
Section: Discussionmentioning
confidence: 99%
“…An interesting cross-sectional questionnaire study of Swedish underground mineworkers showed that familiarity with rescue procedures, cognition of emergencies with injuries, and experience with using equipment influence the preparedness of mineworkers for a peer first response [ 18 ]. There are obvious cognitive barriers to using new safety and health technologies between workers and managers, and the differences are revealed in terms of readiness, cognition, and initial trust with respect to using various technologies [ 19 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Behaviors (primary outcomes) FC: Self-report of whether they shared their genetic test result with at least one family member for the first time or followed up with family (e.g., gave them relevant information, answered questions, etc.) [59] CRM: Self-report risk management behaviors verified via medical records review to determine if they are congruent with current NCCN guidelines [34,60,61] Awareness and engagement in behavior FC: Several items asking whether they have thought about sharing, chosen to share, and attempted to share and follow-up with family members (response options yes, no, unsure) [62] CRM: Single question asking them to pick one of seven statements that best describes where they are in following medical guidelines [63] Capability (objective knowledge) Both: Inherited cancer testing and treatment knowledge (scores range from 0 to 12 correct) [64,65] Capability (understand how to take action, plan & remember) FC: Likert scale questions (know actions to take, know family members at high risk, clear plan of how, find behavior easy, can remember to act) [62,[66][67][68][69][70][71][72] CRM: Likert scale questions (know actions to take, clear plan of how, find behavior easy, remember to act) [62,66,68,72] Opportunity Last, this study leverages existing novel infrastructure that allows for the recruitment of patients that otherwise may be underrepresented in this type of study (i.e., Blacks, rural dwellers, individuals with low socioeconomic status indicators, and males). Leveraging the TCR offers a population-health approach to recruit participants with P/LP variants in inherited cancer genes.…”
Section: Discussionmentioning
confidence: 99%
“…This proposed, integrative approach has not been adequately considered when introducing DRST despite arguments for the development of such a safety, health, and well-being management system to identify and mitigate employee concerns [ 46 , 50 ]. Identifying ways to systematically incorporate DRST is incredibly important to maintaining worker well-being, especially considering findings from previous research, which has shown that the introduction of new technologies without end users in mind can cause uncertainty and lack of trust that negatively impacts not only adoption but also safety behaviors [ 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%